Immunization Status of School Children of Indore Hailing from Different Socioeconomic Status - Madhuri Inamdar; Saurabh Piparsania; Savita Inamdar; Kuldeep Singh (Medsci Publications, 2011)
Background: Although the immunization coverage has increased over the past few years, school age is still a neglected area and accounts for high number of unimmunized children in developing world including India. Objective: This study has been undertaken to determine the immunization status of school children in an urban locality of Indore, a district of central India; and to determine if parental socioeconomic status affect immunization coverage. Material and methods: The study was school based cross-sectional, conducted in 50 schools of Indore district selected by random sampling. Children were between the ages of 5-16 years. Information was collected from parents by providing pre-tested proforma to the students. Result: Only 54.3% of children included in the survey were fully immunized as UIP schedule, while the percentage of partially immunized and unimmunized children was 42.1 and 3.6%, respectively. Conclusion: The percentage of vaccination was significantly proportionate to higher socioeconomic status (p -value <0.0001).